Nadwykonania podmiotów leczniczych w ramach realizacji kontraktów zawartych z NFZ – problematyka związana z opodatkowaniem podatkiem dochodowym - Krawczyk, Michał (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2015)
The purpose of the following article is to introduce and elaborate on the manner in which income and costs arising from the so-called surplus performance of medical services should be treated from the fiscal point of view. Such surplus performances occur when the limit for medical services determined by the agreement between a health care institution and the National Health Fund (NHF) is exhausted. The article briefly outlines the reasons for and the mechanisms behind the phenomenon of surplus performance, and it also attempts to discuss an appropriate method of demonstrating such cases by health care institutions in their income tax settlements, in accordance with the applicable regulations and individual law interpretations issued by tax authorities.
Keywords: podatki dochodowe; przychody; nadwykonania; podmioty lecznicze; świadczenia ponadlimitowe; koszty